Respuesta :
Answer:
X= -7
Step-by-step explanation:
Divide both sides of the equation by 6.
Move the constant to the right.
Add the numbers.
Change the signs.
Answer:
x = -7
General Formulas and Concepts:
Pre-Algebra
Order of Operations: BPEMDAS
- Brackets
- Parenthesis
- Exponents
- Multiplication
- Division
- Addition
- Subtraction
- Left to Right
Equality Properties
Step-by-step explanation:
Step 1: Define
6(-x - 3) = 24
Step 2: Solve for x
- Divide 6 on both sides: -x - 3 = 4
- Add 3 on both sides: -x = 7
- Divide -1 on both sides: x = -7
Step 3: Check
Plug in x into the original equation to verify it's a solution.
- Substitute in x: 6(-(-7) - 3) = 24
- Multiply: 6(7 - 3) = 24
- Subtract: 6(4) = 24
- Multiply: 24 = 24
Here we see that 24 does indeed equal 24.
∴ x = -7 is the solution to the equation.